Language immersion and its role in refining and enriching the linguistic repertoire of non-native learners of Arabic - saighi, souad massouda (El Omda in Linguistics and Discourse Analysis, 2025)
It is well known that the Arabic language has recently gained a high and prestigious status. As a result, many non-native speakers seek to learn it for various reasons. Finding an effective method for learning it has become a concern for many. In this regard, the language immersion program has proven its effectiveness, particularly in enriching the Arabic vocabulary of non-native learners. This vocabulary forms the backbone of both the teaching-learning process and communication in Arabic.